2006
DOI: 10.1002/eji.200425360
|View full text |Cite
|
Sign up to set email alerts
|

Binding of human serum amyloid P componentto L‐selectin

Abstract: Serum concentrations of soluble L-selectin by far exceed those of other soluble adhesion molecules, and serum soluble L-selectin concentrations are remarkably stable upon prolonged storage. We present evidence for Ca 2+ -dependent binding interactions between human serum amyloid P (SAP), a proteolysis-resistant pentraxin glycoprotein, and L-selectin, as shown by surface plasmon resonance measurements, protein band shift assays in a native PAGE system, and after SDS-PAGE and membrane transfer. Monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…However, a different group found that SAP inhibits the binding of human granulocyte to TNFα-stimulated human umbilical vein endothelial cells [59]. In this report, we find that SAP does not act as a granulocyte chemoattractant, tends to decrease granulocyte adhesion, and does not affect the percentage of granulocyte expressing CD11b and CD18.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…However, a different group found that SAP inhibits the binding of human granulocyte to TNFα-stimulated human umbilical vein endothelial cells [59]. In this report, we find that SAP does not act as a granulocyte chemoattractant, tends to decrease granulocyte adhesion, and does not affect the percentage of granulocyte expressing CD11b and CD18.…”
Section: Discussionmentioning
confidence: 40%
“…SAP increases the percentage of neutrophils expressing adhesion molecules such as CD11b and CD18 and the fibronectin receptor α5β1 [58]. In flow chambers, SAP inhibits the binding of human neutrophils to TNFα-stimulated human umbilical vein endothelial cells [59]. Since granulocytes can recognize SAP through Fc receptors, and the reports of the regulation of neutrophil adhesion by SAP seem inconsistent, we examined the effect of SAP on granulocyte adhesion and recruitment to sites of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…SAP binds to human and murine neutrophils and decreases TNF-␣-and IL-8-induced neutrophil binding to ECM components [20,21]. SAP also reduces TNF-␣-induced human neutrophil adhesion to endothelial cells [22]. One possible mechanism underlying the effect of SAP on neutrophils involves SAP binding to, and thus, potentially blocking, the adhesion receptor L-selectin on neutrophils [22].…”
Section: Sap Binds To Neutrophils To Regulate Their Functionmentioning
confidence: 99%
“…When this regulation is compromised, the elevated influx of neutrophils and recruitment of other immune cells by activated neutrophils can cause severe organ damage and fibrosis (1416). SAP binds neutrophils to inhibit their spreading and adhesion to components of extracellular matrix and endothelial cells (12, 17). Injections of SAP decrease the infiltration of neutrophils into the lungs following bleomycin insult in mice (12).…”
Section: Introductionmentioning
confidence: 99%